2018
DOI: 10.1002/cpdd.627
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo‐Controlled, Multiple‐Ascending‐Dose Study to Assess the Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of the Soluble Guanylate Cyclase Stimulator Praliciguat in Healthy Subjects

Abstract: Nitric oxide (NO)‐soluble guanylate cyclase (sGC)‐cyclic guanosine monophosphate (cGMP) signaling is central to the regulation of several physiological processes, including blood flow and inflammation. Deficient NO signaling is implicated in multiple diseases. sGC stimulators are small molecules that enhance sGC activity, particularly in combination with NO. In a randomized, placebo‐controlled phase 1 study, the safety, tolerability, pharmacokinetics, and pharmacodynamics of multiple ascending doses of the sGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 35 publications
5
23
0
Order By: Relevance
“…The QWBA study revealed that praliciguat was widely distributed, which is consistent with the large volume of distribution found for praliciguat in pharmacological studies in the rat ( V ss 10.5 L/kg, 7 and with the apparent volume of distribution in the humans ( V z / F 3100‐3610 L, 8). Tissues with the highest exposure ratios relative to plasma were liver, intestines, adrenal gland, and adipose, and those with the lowest values were seminal vesicle, blood, CNS tissues, lens of the eye, and bone, there was no specific association with melanin in the skin or eye.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The QWBA study revealed that praliciguat was widely distributed, which is consistent with the large volume of distribution found for praliciguat in pharmacological studies in the rat ( V ss 10.5 L/kg, 7 and with the apparent volume of distribution in the humans ( V z / F 3100‐3610 L, 8). Tissues with the highest exposure ratios relative to plasma were liver, intestines, adrenal gland, and adipose, and those with the lowest values were seminal vesicle, blood, CNS tissues, lens of the eye, and bone, there was no specific association with melanin in the skin or eye.…”
Section: Discussionsupporting
confidence: 83%
“…In conclusion, praliciguat is extensively distributed to tissues and is eliminated by phase 1 and phase 2 metabolic pathways. Given the minor contribution of renal elimination, which was confirmed in the clinic, 8 praliciguat exposure is not expected to be altered in patients with impaired renal function. The extensive tissue distribution of praliciguat is unique among clinical‐stage sGC stimulators, and may make praliciguat particularly well suited for the treatment of cardiometabolic diseases with multiorgan involvement.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Praliciguat is an sGC stimulator with a long half-life in preclinical species, extensive tissue distribution, and mainly hepatic clearance (Tobin et al 2018). Its pharmacokinetic half-life in humans is consistent with QD dosing (Hanrahan et al 2018). Praliciguat has completed Phase 1 studies in healthy subjects and Phase 2a exploratory studies in patients with type 2 diabetes and a history of hypertension (NCT02906579, NCT03091920) Praliciguat is currently under investigation for treatment of diabetic nephropathy (NCT03217591) and heart failure with preserved ejection fraction (NCT03254485).…”
Section: Activities Towards Next-generation Sgc Stimulatorsmentioning
confidence: 93%